Reliability of GaAs-based semiconductor diode lasers: 0.6-1.1 mu m - Yellen, S.L.; Shepard, A.H.; Dalby, R.J.; Baumann, J.A.; Serreze, H.B.; Guido, T.S.; Soltz, R.; Bystrom, K.J.; Harding, C.M.; Waters, R.G. (IEEE journal of quantum electronics, 1993)
Results of reliability studies of GaInP (0.6-0.7 mu m); AlGaAs, InAlGaAs, and InGaAsP (0.81 mu m); GaAs (0.86 mu m); and InGaAs (0.9-1.1 mu m) quantum-well laser diodes are summarized. Conclusions drawn from over one million cumulative lifetest hours and substantial electron-beam-induced-current (EBIC) failure analysis are presented. Improvements in laser reliability with the addition of indium (in both sudden failures and gradual degradation) and with the elimination of aluminium (in gradual degradation) have been observed. These trends, combined with the observed inconsequential effect of strain, provide guidelines for the design of highly reliable lasers.< >